A Study of Customer's Expectations Towards Depository Participants of Ludhiana City - Sofat, Rajni; Hiro, Preeti (Indian Journal of Finance, 2009)
The Indian capital market is undergoing a big transformation. A fully computerized online trading system is now replacing the old manual system of trading and settlement requiring handling of huge volume of papers. So for the setting up of a depository and formation of scrip less trading and settlement, government of India promulgated the depository act 1995, which was later, replaced by depositories act, 1996. The main objective of this study is to compare the working of various DP's in Ludhiana, to understand the customer's expectations from DP's, to measure their satisfaction level. And to find out the factors that influence the choice of a particular DP. This study has been undertaken to perform a comparison of various depository participants in Ludhiana and customer's perception about their working. Primary data has been collected through a structured questionnaire as well as by personal interviews with managers and account holders. Chi- square test has been applied to find out the significant relationship between independent variable and dependent variable. It was found from the study that LSE securities is a new star in the DP market and will emerge as an undisputed leader in coming years.